Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction